2016
DOI: 10.1007/s00704-015-1729-y
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of summer monsoon precipitation over the Indochina Peninsula in association with ENSO

Abstract: The interannual variability of summer monsoon precipitation over the Indochina Peninsula (ICP) is characterized using the first empirical orthogonal function of 5-month total precipitation (May to September). The leading mode, with a monopole pattern, accounts for 30.6 % of the total variance. Dynamic composites and linear regression analysis indicate that the rainy season precipitation over the ICP is linked to El Niño-Southern Oscillation (ENSO) on interannual scales. The preceding winter [D(−1)JF(0)] negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…. Given that ENSO has a significant influence on the SCSSM [3,[10][11][12][13][14], the question naturally arises as to whether ENSO could also have an impact on the relationship between the VM and SCSSM. To answer this question, we computed the partial correlation between the FMA VMI and the following JAS SCSSMI by removing the effect of the previous winter (DJF)'s ENSO signal (represented by the Niño3.4 index).…”
Section: Relationship Between the Vm And Scssmmentioning
confidence: 99%
See 2 more Smart Citations
“…. Given that ENSO has a significant influence on the SCSSM [3,[10][11][12][13][14], the question naturally arises as to whether ENSO could also have an impact on the relationship between the VM and SCSSM. To answer this question, we computed the partial correlation between the FMA VMI and the following JAS SCSSMI by removing the effect of the previous winter (DJF)'s ENSO signal (represented by the Niño3.4 index).…”
Section: Relationship Between the Vm And Scssmmentioning
confidence: 99%
“…The mechanisms by which the extratropical atmospheric variability over the North Pacific influences the tropical Pacific SST anomalies have been extensively discussed [42][43][44][45][46][47]. It is proposed that the extratropical atmospheric variability can initiate a basin-scale SST structure Given that ENSO has a significant influence on the SCSSM [3,[10][11][12][13][14], the question naturally arises as to whether ENSO could also have an impact on the relationship between the VM and SCSSM. To answer this question, we computed the partial correlation between the FMA VMI and the following JAS SCSSMI by removing the effect of the previous winter (DJF)'s ENSO signal (represented by the Niño3.4 index).…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have concentrated on the assessment of different reanalysis products and have shown that reanalysis data sets can effectively reduce the biases caused by the inhomogeneous distribution of observation stations (Simmons et al, 2004;Sylla et al, 2010;Cai et al, 2014). The performance of reanalysis data sets have been evaluated and compared with data from observation stations or other reliable sources (Screen and Simmonds, 2011;Cornes and Jones, 2013;Ge et al, 2017).…”
mentioning
confidence: 99%
“…Many researchers indicated that the El Niño -Southern Oscillation (ENSO) cycles have influenced Thailand monsoon rainfall on interannual scales [5][6][7][8], [10][11][12][13][14]. The variations in the position and intensity of the ITCZ are associated with climate phenomena known as the ENSO.…”
Section: Introductionmentioning
confidence: 99%